2016
DOI: 10.29333/ejgm/81897
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of asthma and COPD patients in emotional status: A cross-sectional study.

Abstract: Background: Psychiatric comorbidities are prevalent in patients with chronic respiratory diseases. But, there is no clear evidence comparing asthma and COPD. The aim of the present study was to investigate and compare the emotional status of patients with asthma and COPD Methods: The study included 132 consecutive patients who were diagnosed with asthma (n=78) and COPD (n=54) who did not receive therapy for pshiciatric disorders. Emotional status were evaluated using the Beck and Hamilton surveys. Results: The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Several studies have shown increased prevalence of psychiatric disorders in asthma patients and other somatic chronic illnesses [1][2][3][4][5][6][7][8]. Psychiatric co-morbidity in asthma can take many forms, including panic disorder, posttraumatic stress disorder, generalized anxiety disorder, persistent depressive disorder, depression and other conditions, both current and in the past [9][10][11].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown increased prevalence of psychiatric disorders in asthma patients and other somatic chronic illnesses [1][2][3][4][5][6][7][8]. Psychiatric co-morbidity in asthma can take many forms, including panic disorder, posttraumatic stress disorder, generalized anxiety disorder, persistent depressive disorder, depression and other conditions, both current and in the past [9][10][11].…”
mentioning
confidence: 99%
“…The estimated general population prevalence of mental health concerns in children and adolescents ranges from 0.6% to 4.7%, whereas many studies have shown a higher prevalence in children and adolescents with asthma [2]. Asthma can be associated with a two-fold increase in the likelihood of a panic attack in the child/adolescent population, and up to one third of child/adolescent asthmatics may meet the criteria for anxiety disorders [2,8]. For the general adult population, the estimated range of anxiety disorders varies between 1% and 3%, whereas the prevalence in the patients with asthma is estimated at 6.5% to 24% [2].…”
mentioning
confidence: 99%